Nitrogen Balance of Effluent Irrigated Silage Cropping Systems in Southern Australia - Chris J. Smith; Val O. Snow; Ray Leuning; David Hsu (The Scientific World Journal)
The nitrogen (N) balance in a double-cropped, effluent spray irrigation system was examined for several years in southern Australia. The amounts of N added by irrigation, removed in the crop, and lost by ammonia (NH3) volatilisation, denitrification, and leaching were measured. Results from the project provide pig producers with the knowledge necessary to evaluate the efficiency of such systems for managing N, and enable sustainable effluent reuse practices to be developed. Oats were grown through the winter (May to November) without irrigation, and irrigated maize was grown during the summer/autumn (December to April). Approximately 18 mm of effluent was applied every 3 days. The effluent was alkaline (pH 8.3) and the average ammoniacal-N (NH4+ + NH3) concentration was 430 mg N/l (range: 320 to 679 mg N/l). Mineral N in the 0- to 1.7-m layer tended to increase during the irrigation season and decrease during the winter/spring. About 2000 kg N/ha was found in the profile to a depth of 2 m in October 2000. N removed in the aboveground biomass (oats + maize) was 590 and 570 kg N/ha/year, equivalent to ≈25% of the applied N. Average NH3 volatilisation during the daytime (6:00 to 19:00) was 2.74 kg N/ha, while volatilisation at night (19:00 to 6:00) was 0.4 kg N/ha, giving a total of 3.1 kg N/ha/day. This represents ≈12% of the N loading, assuming that these rates apply throughout the season. The balance of the N accumulated in the soil profile during the irrigation season, as 15N-labelled N studies confirmed. The high recovery of the 15N-labelled N, and the comparable distribution of 15N and Br in the soil profile, implied that there was little loss of N by denitrification, even though the soil was wet enough for leaching of both tracers.